Twinning in muskox and the cytogenetic investigation of a freemartin - Reindl, N. J.; Buoen, L. C.; Zhang, T. Q. (Rangifer, 1993)
The occurrence of twinning has been documented for muskox in both wild and captive populations. Of two known captive twin births only one set survived beyond 120 days. In both cases the twins were male-female pairs and both females showed abnormal sexual development. Two sets of stillborn twins have also been recorded. All four stillborn fetuses were female and none showed anomalies of the reproductive tract upon post-mortem examination. Blood cultures from the surviving male and female twins revealed that both were chimeric, indicating the admixture of fetal blood. Fibroblast cultures were normal for the respective sex of each individual. The freemartin heifer had anatomical abnormalities of the clitoris as well as the secondary sex characteristics of a male.